PENGARUH DER DAN DPR TERHADAP PBV PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Susilawati Susilawati (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2026)
This study aims to analyze the effect of the Debt to Equity Ratio (DER) and Dividend Payout Ratio (DPR) on Price to Book Value (PBV) in food and beverage companies listed on the Indonesia Stock Exchange during the 2010–2019 period. The study employed an associative method with a quantitative approach. The research sample consisted of 10 companies selected using a purposive sampling technique, with secondary data obtained from the companies’ financial statements. Data analysis was conducted using multiple linear regression to examine both the partial and simultaneous effects of the variables. The results indicate that DER has a positive effect on PBV, suggesting that an effectively managed capital structure can enhance market perceptions of firm value. DPR was also found to have a positive effect on PBV, indicating that dividend distribution policies serve as a positive signal for investors in assessing the company’s prospects. Simultaneously, DER and DPR contribute to improving PBV, leading to the conclusion that financing decisions and dividend policies are important factors in shaping firm value in the food and beverage sector. These findings emphasize the importance of appropriate financial strategies to increase investor confidence and strengthen the company’s position in the capital market.